(untitled) - Radebaugh, Lee H. (New York, 1997)
The book is divided into six different parts: Part 1 contains the introductory chapters to the book that are designedto set up the international business environment in which international accounting functions. Chapter 1 introduces the history of accounting and international business and provides an overview of the text. Chapter 2 discusses the nature of international business, global trade and investment patterns, the major players in international markets, and global startegy. Part 2 includes chapters 3-7 and discusses comparative accounting and international harmonization. In this part, the book discusses the environmental influences on accounting and control systems, with spacial emphasis on how accounting system and practices are influenced by the environment. Part 3 includes chapters 8-13, and focuses on a variety if international financial reporting issues such as international business combinations and consolidations, accounting for goodwill and intangibles, international segmental reporting, accounting for price changes and inflation, and accounting for foreign currency transactions and the translation of foreign currency finacial statements. Part 4 includes chapters 14 and 15, and introduces the concepts of international financial analysis. Part 5 includes chapters 16-18, and covers international management accounting control. Part 6 completes the book and includes chapters 19-21: international taxation, external auditing of foreign operation, and global accounting issues into the twenty-first century
Keywords: Accounting